Oxidative stress and alopecia areata - Ma, Yi-qian; Sun, Zhan; Li, Yu-Mei; Xu, Hui (Frontiers in Medicine, 2023)
Alopecia areata (AA) is an inflammatory autoimmune disease characterized by non-scarring hair loss on the scalp or any other part of the hair-bearing skin. While the collapse of the immune privilege is considered as one of the most accepted theories accounting for AA, the exact pathogenesis of this disease remains unclear by now. Other factors, such as genetic predisposition, allergies, microbiota, and psychological stress, also play an important role in the occurrence and development of AA. Oxidative stress (OS), an unbalance between the oxidation and antioxidant defense systems, is believed to be associated with AA and may trigger the collapse of hair follicle-immune privilege. In this review, we examine the evidence of oxidative stress in AA patients, as well as the relationship between the pathogenesis of AA and OS. In the future, antioxidants may play a new role as a supplementary therapy for AA.